DISCOVERY LEARNING BERBASIS FLIPPED CLASS TERHADAP AKTIVITAS DAN PENGUASAAN KONSEP - Klotilda Jenirita; Nurul Ain; Chandra Sundaygara (RAINSTEK : Jurnal Terapan Sains & Teknologi, 2021)
This study aims to determine the effect of the flipped class-based discovery learning model on students' activities and conceptual mastery. The population in this study were all students of class VIII SMP Negeri 02 Singosari Malang. Sampling using purposive sampling technique. The sample chosen was class VIII A as the experimental class with 28 students and class VIII B as the control class with 29 students. The research design used was a quasi experiment and the research design used a postets only control group design. The data analysis used two-way ANOVA. Based on the results of the research that has been done, it is found that there is an effect of the discovery learning model based on flipped class on students' activities and conceptual mastery.